Effect of sexual counseling based on the PLISSIT model on the quality of sexual life and emotional divorce of hemodialysis patients in the special diseases center of Birjand City in Iran: Short Communication - Eshrat Saeedi bazkhane; Hamideh Hosseini; Marzieh Torshizi (مجله دانشگاه علوم پزشکی بیرجند)
Considering the sexual problems in hemodialysis patients and the need for intervention in this regard, this study aimed to investigate the effect of sexual counseling based on the Permission, Limited Information, Specific Suggestions, and Intensive Care (PLISSIT) model on the quality of sexual life and emotional divorce of hemodialysis patients. This semi-experimental randomized controlled study was conducted on 60 hemodialysis patients who met the inclusion criteria of the study. The intervention group received sexual counseling based on the PLISSIT model, and the control group received only routine care. The standard questionnaire on sexual life quality and emotional divorce by Gottmann was completed before and one month after the intervention. The average score of the quality of sexual life and emotional divorce in the intervention group showed a significant increase after the intervention compared to before the intervention (P<0.001); however, the difference before and after in the control group was not significant. According to the results of this study, sexual counseling based on the PLISSIT model had a positive effect on the quality of sexual life of hemodialysis patients and also emotional divorce. Therefore, this training can be useful and effective in solving the sexual problems of dialysis patients.